Subinhibitory Concentrations of Biogenic Silver Nanoparticles Affect Motility and Biofilm Formation in Pseudomonas aeruginosa - Saeki, Erika Kushikawa; Yamada, Amanda Yaeko; de Araujo, Larissa Amianti; Anversa, Laís; Garcia, Doroti de Oliveira; de Souza, Renan Luiz Barros; Martins, Heloísa Moreira; Kobayashi, Renata Katsuko Takayama; Nakazato, Gerson (Frontiers in Cellular and Infection Microbiology, 2021)
Biogenic silver nanoparticles (bio-AgNPs) are increasingly recognized as an antibiofilm and antivirulence strategy against P. aeruginosa, a bacterium that causes chronic infections in immunocompromised and cystic fibrosis patients. This study aimed to investigate the effects of subinhibitory concentrations of bio-AgNPs on motility and biofilm formation in P. aeruginosa. Bio-AgNPs were synthesized via reduction of ionic silver catalyzed by cell-free culture filtrate from Fusarium oxysporum. A total of 17 P. aeruginosa isolates and strains were evaluated for swarming, swimming, and twitching motility in the presence and absence (control) of bio-AgNPs, including 10 clinical isolates from patients with and without cystic fibrosis, 5 environmental isolates obtained from the public water supply system, and 2 reference strains (PAO1 and PA14). Isolates were identified by biochemical and molecular methods. Minimum inhibitory concentrations (MICs) were determined by the broth microdilution method. Swarming, swimming, and twitching motility assays were performed in Petri dishes. Biofilm formation capacity was assessed quantitatively by the crystal violet method. MIC values ranged from 15.62 to 62.50 µM. The results showed that subinhibitory concentrations of bio-AgNPs (½ MIC, 7.81–31.25 µM) significantly increased (p < 0.05) swarming, swimming, and twitching motility in 40.0, 40.0, and 46.7% of isolates, respectively. Subinhibitory bio-AgNP treatment enhanced (p < 0.05) biofilm formation capacity in PA14 and a cystic fibrosis isolate (P11). It is concluded that subinhibitory concentrations of bio-AgNPs increased biofilm formation and swarming, swimming, and twitching motility in PA14 and some P. aeruginosa isolates. These virulence factors are directly involved with quorum-sensing systems. Further research should investigate the effects of AgNPs on P. aeruginosa quorum sensing to help elucidate their mechanism of action at subinhibitory concentrations.